Surgical Resection of Intraocular Tumors (Partial Transscleral Sclerouvectomy Combined With Mircoinvasive Vitrectomy and Reconstruction of the Eyeball) in Asian Patients: Twenty-Five Years Results - Zhou, Nan; Wang, Ping; Xu, Xiaolin; Liu, Yueming; Wei, Wenbin (Frontiers in Oncology, 2022)
Objective: To describe the outcome of intraocular tumor resection by partial transscleral sclerouvectomy (PTSU) combine with mircoinvasive vitrectomy and reconstruction of the eyeball (MVRE) in Asian patients. Design and methods: This retrospective, interventional cohort study included 366 patients who underwent PTSU combine with MVRE for intraocular tumors of the adult and pediatric age groups. Main Outcome Measures: Globe salvage, best corrected visual acuity (BCVA), surgical side effects, tumor control, and tumor-related metastasis and death. Results: The mean follow-up was 87 months (median, 66; range, 1-303). Among the 366 patients, the mean age was 8.5 years (median, 7; range, 1-19) in 37 pediatric patients, and was 43 years (median, 42; range, 20-51) in 329 adult patients. The common pathologic diagnosis of the 366 patients including: In the pediatric age group, medulloepithelioma (8/37), melanocytoma (13/37); In the adult group, melanoma (195/329), RPE adenoma (21/329), nonpigmented epithelium adenoma (19/329), melanocytoma (24/329), and leiomyoma (9/329). The globe salvage rate was 81.1% in the pediatric age groups (<20 years), and 93.6% in the adult group (≥20 years), respectively. Of the 338 salvaged eyes, final BCVA was 20/20 to 20/40 in 16 (4.7%), 20/40 to 20/80 in 58 (17.2%), 20/80 to 20/200 in 160 (47.3%), and≤20/200 in 104 (30.8%). Early side effects included corneal edema in 28 (7.7%), hyphema in 46 (12.6%) and vitreous hemorrhage in 76 (21%). Postoperative side effects included proliferative vitreoretinopathy (PVR) in 67 (18.3%), late cataract in 42 (11.5%), glaucoma in 18 (5%). Local tumor recurrence was detected in 20 cases (5.5%) at mean interval of 23.6 months, including melanoma (n=19) and medulloepithelioma (n=1). Enucleation was necessary in 28 (7.7%) cases for recurrence in 15 (53.6%), prophylactic in eyes with high-grade malignancy in 5 (17.8%), and for blind painful eye in 8 (28.6%). Kaplan-Meier estimated of the 5, 10-year metastasis rate and metastasis related death (95%CI) in 213 UM patients were 3.2% (1.4%-7.0%), 6.9% (3.8%-12.3%); and 3.5% (1.6%-7.6%), 7.6% (4.2%-13.5%), respectively. Conclusions: PTSU combine with MVRE offers several theoretical advantages over enucleation and radiotherapy. It can achieve control of most intraocular tumors, preserve useful vision, and maintain a cosmetically normal eye.